2014
DOI: 10.1002/2013ja019568
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of equatorial plasma mass densities deduced from field line resonances observed at ground for dipole and IGRF models

Abstract: The technique to remotely sense the plasma mass density in magnetosphere using field line resonance frequencies detected by ground-based magnetometers has become more and more popular in the last few years. In this paper we examine the error that would be committed at low and middle latitudes (L < 4) in estimating the equatorial plasma mass density if dipole field lines are assumed instead of the more realistic representation given by International Geomagnetic Reference Field (IGRF) lines. It is found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Linear mode conversion from MHD fast modes to Shear Alfvén eigenmodes occurs at locations within the magnetosphere where the MHD fast mode driver frequency matches the Shear Alfvén wave eigenfrequency, forming highly localized features known as field line resonances (FLRs) (Allan & Poulter, 1992;Rae et al, 2005;Walker, 2000). These have been used to determine the equatorial cold plasma density from ground-based observations (Dent et al, 2006;Vellante, Piersanti, Heilig, et al, 2014;Vellante, Piersanti, & Pietropaolo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Linear mode conversion from MHD fast modes to Shear Alfvén eigenmodes occurs at locations within the magnetosphere where the MHD fast mode driver frequency matches the Shear Alfvén wave eigenfrequency, forming highly localized features known as field line resonances (FLRs) (Allan & Poulter, 1992;Rae et al, 2005;Walker, 2000). These have been used to determine the equatorial cold plasma density from ground-based observations (Dent et al, 2006;Vellante, Piersanti, Heilig, et al, 2014;Vellante, Piersanti, & Pietropaolo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As regards the geomagnetic field model, a dipole ap− proximation has been usually adopted for deriving the equatorial density from FLRs detected at low and mid latitudes (L < 4) [e.g., Menk et al, 1999;Berube et al, 2005;Villante et al, 2006;Chi et al, 2013;Wang et al, 2013]. Vellante et al, [2014a], however, found that the use of the dipole model at these latitudes may result in an error in the inferred density appreciably larger than what is usually assumed, up to 40% at L = 2 when com− pared with the results obtained using the International Geomagnetic Reference Field (IGRF) model. At higher latitudes, the currents associated with the DEL CORPO ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…Their leading edges usually drive shock waves, called interplanetary shocks (ISs; Araki & Shinbori, ; Lugaz et al, ; Oliveira et al, ; Piersanti et al, ). The impact of IS onto the magnetopause compresses the magnetosphere (Vellante et al, ; Villante & Piersanti, , ), causing a sudden increase in the geomagnetic field intensity, called a Sudden Impulse (SI), often followed by intense fluctuations of the magnetospheric field (Di Matteo & Villante, ; Piersanti et al, ; Villante et al, ; Zhang et al, ). While traveling in the interplanetary space, ICMEs carry magnetic structures, often recognizable as magnetic clouds (MC), which are characterized by an intense magnetic field whose north‐south component smoothly rotates (Gosling, ; Shen et al, ).…”
Section: Introductionmentioning
confidence: 99%